Longitudinal study of mental health and pain-related functioning following a motor vehicle collision - Valentine, Sarah E. (Health Psychol, 2016)
OBJECTIVE: Relations between mental and physical health symptoms are well-established in the literature on recovery following motor vehicle collisions (MVCs). To understand the temporal sequencing and evolution of these relations, we examined the bidirectional association between mental and physical health symptoms at 4 and 16 weeks following a MVC. METHODS: The sample consisted of 103 participants recruited through public MVC police reports. The study included self-report assessments for posttraumatic stress symptoms, depressive symptoms, bodily pain, and role limitations due to physical health. A series of multivariable linear regression analyses were conducted to estimate the associations between these mental and physical health outcomes. RESULTS: The analysis revealed that mental health symptoms at 4 weeks post-MVC were associated with higher bodily pain at 16 weeks post-MVC (PTSD symptoms: β=−0.74, 95% CI: − 1.06, −0.42; depressive symptoms: β= −1.34, 95% CI: −1.90, −0.78), but not higher health-related role limitations. Physical health symptoms at 4 weeks post-MVC were not associated with PTSD or depressive symptoms at 16 weeks post-MVC. CONCLUSIONS: The results indicate the predictive strength of mental health symptoms at 4 weeks post-MVC in identifying individuals at risk for bodily pain at 16 weeks and shed light on the temporal sequencing of how relations between physical and mental health symptoms emerge over time. This suggests that early assessment of mental health symptoms may have significant implications for the treatment of these patients.